DIGITAL STORYBOOK TO IMPROVE WRITING NARRATIVE: THE TTW STRATEGY PRESENTED AND TESTED - Tatik Irawati (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2018)
Internet activity is an ICT (Information, Communication and Technology) provides opportunities for students in learning through digital story books that are presented in an interesting way and directly contribute to the improvement of the ability to write narrative. The think-talk-write strategy (TTW) is based on the development of thinking skills, verbal and written communication. The flow of progress of this strategy starts from the involvement of students in thinking or dialogue with themselves after the process of reading the story and share ideas with friends before writing. This research used collaborative classroom action research designs, researchers and teachers worked together in conducting research. This study was carried out in a series of cycles that refer to class action research procedures namely, planning, implementing, observing, and reflecting. The research data was collected through several instruments, namely the students' writing sheets, questionnaires, and observation checklist. The subjects of this study were 30 seventh graders of junior high school. The average value obtained during the preliminary study was 62. The value increased to 75 in cycle 1. In cycle 2, the average value obtained increased again to 80.5. The use of digital storybook is highly recommended to improve the ability to write narrative.